Statistical Physics Modeling of Sorption Isotherms of Aluminum, Iron, and Indium on Tetraphenylporphyrin (H2TPP) and Tetrakis(4-tolylphenyl)porphyrin (H2TTPP): Phenomenological Investigation of Metalloporphyrins at the Molecular Level - Zainab Elqahtani; Mohamed Ben Yahia; Nada Alfryyan; Shatha Aldaghfag; Fatma Aouaini (Adsorption Science & Technology)
A quartz crystal adsorbent functionalized with two promising porphyrins (the 5,10,15,20-tetrakis(4-tolylphenyl)porphyrin and the 5,10,15,20-tetraphenylporphyrin) was applied for the investigation of the adsorption phenomenon of aluminum chloride, iron chloride, and indium chloride. The aim is to prove new insights about the appropriate adsorption materials for metalloporphyrin fabrication. The equilibrium isotherms were measured at five adsorption temperatures (from 290 to 330 K) through the microbalance (QCM) method. The discussion of the experimental observations indicated that the adsorption of the aluminum chloride and the iron chloride was performed via a monolayer process. On contrary, the participation of the chloride ions in the double-layer adsorption of the indium chloride was explained by the layer-by-layer process. Overall, the statistical physics modeling of the experimental curves indicated that the number of ions per adsorbent site n was found inferior to 1 for all the adsorption systems (multi-interaction process for the three ions). Interestingly, the physicochemical investigation of the three adopted models showed that the complexation mechanism of the tested porphyrins was an endothermic process since the two steric parameters (n and PM) increased with the rise of the temperature. The FeCl3 curves were discussed via a monolayer adsorption model which includes the parameters a and b (lateral interaction description), indicating the lowest stability of the formed iron-porphyrin complex. The energetic study showed that the adsorption energies ∣−ΔE1/2∣ of AlCl3 on H2TTPP and H2TPP are superior to 40 kJ/mol (chemical adsorption mechanism), whereas the adsorption mechanisms of FeCl3 and InCl3 took place via a physical process since they presented adsorption energy values lower than 40 kJ/mol.